Masson's tumor of the parotid gland: A case report and literature review - Fawaz Alotaibi; Abdulrahman Hesham; Marwa Hatem; Yousef Alshamrani; Areil Cuevas Ocampo; Chinedum Okafor (Oral and Maxillofacial Surgery Cases)
Masson's tumor, also known as intravascular papillary endothelial hyperplasia (IPEH), is a rare benign vascular lesion characterized by an abnormal proliferation of endothelial cells within blood vessels, forming papillary structures that can occur in various parts of the body, including the parotid gland. Masson's etiology and risk factors remain unclear, but trauma and vascular pathological conditions may contribute to tumor progression. Despite its benign nature, Masson's tumor can present diagnostic challenges due to its variable clinical presentation and the need to differentiate it from other vascular lesions and malignancies. This case report presents a rare occurrence of Masson's tumor in the parotid gland of a 39-year-old female patient, along with a comprehensive review of the existing literature of this unusual presentation.